(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
As one of the most significant types of figurative thinking, which are categorized by thematic groups, the article explains the core of the symbol, its characteristics, and its relevance in public life through examples. Folklore and a system of symbolic images that have been employed in literature for centuries form the foundation of traditional symbols.